Magnetic biochar as dual-functional mediator for low-field magnetic separation of vivianite and membrane fouling mitigation in anaerobic membrane bioreactors - Feng-Ai Yang; Ying Dong; Jifei Chang; Rong Chen; Xin Wang; Juncheng Liu; Fernanda Leite Lobo; Devard I. Stom; Nan Li (Bioresource Technology, 2026)

Excavatolide E triggers oxidative stress-associated apoptosis and DNA damage to inhibit bladder cancer cell proliferation - Che-Wei Yang; Chia-Hung Yen; Tsu-Ming Chien; Szu-Yin Yu; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (Molecular Biology Reports, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Investigating the mechanisms of liver injury in zebrafish induced by polystyrene microplastics and 17α-methyltestosterone based on the gut-liver axis - Weiya Rong; Zijun Xiong; Chang Hu; Haiyan Zhao; Lu Cao; Jiaoxin Xie; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Environmental Pollution, 2026)

Structural evolution and reaction pathways of hematite reduction by biomass-lignin derived bio-coke - Kefeng Wu; Lichao Ge; Lei Yao; Chunxia Yang; Nai Rong; Yanquan Liu; Yang Wang; Chang Xu (Bioresource Technology, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Regional assessment of multi-pool mangrove carbon across five coastal provinces of China: Heterogeneity, carbon accounting, and contextual screening - Yan Zheng; Wenhai Lu; Chang Liu; Hefeng Wang; Rong Zeng; Yan Xu; Yangyi Ai (Regional Studies in Marine Science, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Glacial pacing and monsoon modulation of multi-scale lacustrine carbon sequestration in the Weihe Basin, North China - Yili Long; Xiaoqing Rong; Hang Zhang; Hai Xu; Yougui Song; Hong Chang; Xiaoke Qiang; Li Ai; Xingxing Liu; Youbin Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

The poisoning mechanism of N2O reductive catalysts and anti-interference modification/regeneration technology - Wu Pengfei; Guan Bin; Zhu Lei; Zhu Tiankui; Chang Shiying; Ma Jiangli; Wang Rong; Yang Dongxia; Shu Kaiyou; Zhuang Zhongqi; Chen Junyan; Gao Junjie; et al. (Journal of Environmental Chemical Engineering, 2026)

Insights into performance and mechanism of VS2@Fe3O4 magnetic nano-composite as heterogeneous catalyst of peroxymonosulfate for phthalate esters degradation - Xue Rong; Hongying Wang; Jing Chang; Zhongpeng Wang; Qigang Gao; Yanhao Wang; Dong Ma (Journal of Environmental Chemical Engineering, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

Temporal changes of soil erodibility and its driving factors in long-term sugarcane continuous cropping systems - Juan Wei; Tieguang He; Yu Zhu; Lirong Su; Huiping Ou; Yingying Deng; Mengge Yang; Jinlong Chang; Yuliang Liao; Qingbiao Rong; Yuhan Huang (CATENA, 2026)

High-throughput toxicological profiling and ToxPi-based prioritization of chemical migrants from recycled paper used in food contact materials - Pei-Shan Chih; Pei-Chun Hsu; Rachelle D. Arcega; Wei-Hsiang Chang; Pei-Chu Tai; Ching-Chang Lee; Trias Mahmudiono; Wan-Ru Wang; Rong-Jane Chen; Hsiu-Ling Chen (Journal of Hazardous Materials, 2026)

Synergistic management of nitrogen-based pollutants from ammonia-fueled engines: key emission control technologies - Junjie Gao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Perfluorohexane sulfonate (PFHxS)-induced energy metabolism disruption in Chlorella pyrenoidosa: Integrating physiological and transcriptomic insights - Biao Liao; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Shan Liu; Ji-Xun Chen; Liu-Yi Wei; Xiang-Rong Xu; Kefu Yu (Environmental Pollution, 2026)

In situ polymerization-prepared water-stable CsPbX3/PMMA composites for water-stimulated anti-counterfeiting and bioimaging - Rong Huang; Xiaoman Xiang; Danxia Zheng; Geyu Feng; Xinyu Ge; Rongze Zhu; Peng Chen; Xueling Chang; Xiao-Chun Hang; Xiaoyang Qi; Longfei Ruan (Chemical Engineering Journal, 2026)

Moderate grazing disturbance enhances network stability and ecological functions of rhizobacteria in Alpine meadows: Identification and validation of Core genera - Hainian Lu; Jiaoyang Du; Yongli Xie; Dingan Gao; Xiaohui Wu; Feifei Chang; Liyang Duan; Xuerui Wang; Rong Wang (CATENA, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Nitrogen enrichment alters the relationship between grassland biodiversity and ecosystem multifunctionality: A global meta-analysis - Tao Chang; Huakun Zhou; Hongye Su; Zeying Yao; Cuoji Peng; Hengkang Xu; Yuping Rong; Xinqing Shao (Agriculture, Ecosystems & Environment, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Evaluating the effectiveness of marine ecological red lines: an integrated assessment of ecological outcomes and governance performance - Rong Zeng; Wenhai Lu; Chengliang He; Jie Liu; Yan Xu; Chang Liu; Yangyi Ai; Yan Zheng (Frontiers in Marine Science, 2026)
Marine protected areas worldwide often exhibit uneven conservation outcomes, largely due to differences in governance effectiveness and management implementation. As a large-scale spatial conservation policy, Marine Ecological Red Lines (MERLs) have been widely implemented in China to regulate human activities and safeguard critical marine ecosystems. However, their protection effectiveness remains insufficiently evaluated using quantitative and scalable approaches. In this study, we develop an indicator-based assessment framework grounded in the Pressure–State–Response (PSR) model to evaluate the effectiveness of MERLs. The framework integrates indicators of anthropogenic pressures, ecosystem conditions, and management responses, enabling spatially explicit and temporally comparable assessment. We apply this framework to MERLs in Hainan Province over a five-year period (2020–2024) and conduct systematic comparisons with adjacent non-protected areas. Furthermore, correlation analysis is used to examine the relationships between pressure reduction and ecological state changes, providing preliminary insight into the associations between management actions and ecological outcomes. The results show that MERLs are associated with reduced anthropogenic pressures and improved ecological conditions relative to surrounding areas, although spatial heterogeneity in outcomes persists. The proposed framework provides a structured approach for examining interactions among pressures, ecosystem states, and governance responses, and provides quantitative evidence supporting conservation effectiveness assessment at a provincial scale. The proposed framework may also support adaptive management and policy optimization for MERLs and provide practical reference for the implementation of Other Effective Area-Based Conservation Measures (OECMs).

Lightweight host materials for practical lithium–sulfur batteries - Chang Zhang; Rong Kou (Science Bulletin, 2026)

A refined stratigraphic framework for the Tremadocian–Floian stage boundary (Lower Ordovician) in the North China Block - Xiang-Ri Chi; Guan-Zhou Yan; Mikael Calner; Fang-Yi Gong; Xiao-Cong Luan; Rong-Chang Wu (Palaeoworld, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Low temperature selective catalytic oxidation of ammonia reaction (NH3-SCO): Introducing Co, or Zr to improve comprehensive performance of the Ag/Al2O3 catalyst - Sikai Zhao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Hazardous Materials, 2026)

Ultraviolet irradiation restores anammox sludge activity from sulfamethazine inhibition by activating energy reallocation and metabolic pathway shifts - Jin-Luo Pang; Rong-Rong Chang; Kai-Yue Dong; Bao-Cheng Huang; Ren-Cun Jin (Journal of Environmental Sciences, 2026)

Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zheng Huang (Fuel, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Corrigendum to “Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control” [Fuel 418 (2026) 138729] - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Corrigendum to “Synergistic management of nitrogen-based pollutants from ammonia-fueled engines: key emission control technologies” [JFUE_138780 (2026) 260529-018277] - Junjie Gao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Ion-gas synergistically reshape microenvironment for bone immune regulation and osteogenic regeneration - Kun Wang; Zhenhua Wang; Bing Xiao; Chang Cai; Jiaqiang Zhang; Yifan Zhang; Liuzhi Wu; Yelin Wu; Ke Rong; Xiaoxing Xie; Guohua Xu (Chemical Engineering Journal, 2026)

Multi-technique NMR analysis of liquid CO2 hydrate growth and pore structure evolution in sediments - Yu-Hao Bu; Yi-Fei Sun; Xiao-Cun Ma; Ling-Ban Wang; Zhen-Bin Xu; Yong-Yi Zhai; Jin-Rong Zhong; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Discovery of pyrrolo[2,3-d]pyrimidine derivatives with inhibitory effect on liver cancer stem cell - Xuecong Zhang; Xuechun Chen; Liwei Wang; Yiyuan Chang; Jiaxin Li; Jijian Yang; Dongxuan Ni; Ruihan Zhang; Rong Liu; Weilie Xiao (Medicinal Chemistry Research, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Review: From research progress to real-world marine applications of direct seawater electrolysis for hydrogen production - Yao Yao; Bin Guan; Lei Zhu; Tiankui Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Nitrous oxide emissions, impacts and treatment technologies: Core progress and prospects of systematic, practical and applicable studies - Luoxin Xu; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

LC-HRMS profiling of processing-induced formation of carcinogenic N-nitrosamines in Areca nut products - Yuan-Jhe Chang; Hsueh-Ju Lu; Yet-Ran Chen; Yi-Jhen Wang; Rajendra Bose Muthukumaran; Chiung-Wen Hu; Mu-Rong Chao (Food Chemistry, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

A colorimetric/fluorescent/electrochemical tri-modal biosensor based on dual CRISPR/Cas12a system for detection of microRNA - Hehua Zhang; Huan Zhu; Hongmin Gao; Yang Zhou; Longbin Que; Shengzhong Rong; Hongkun Ma; Dong Chang; Hongzhi Pan (Analytica Chimica Acta, 2026)

Nutrient input strategies mediate the link of rhizosphere soil microbiomes with rice productivity: Based on a decade-long field experiment - Ning Su; Xiangmin Rong; Qiaorong Li; Yansong Xiao; Guixian Xie; Chang Tian; Yali Kong; Yuping Zhang; Gongwen Luo (Agriculture, Ecosystems & Environment, 2026)

Key genes for ergothioneine biosynthesis and stress adaptation in Schizophyllum commune - Jia Chen; Shuang Leng; Shui-Yun Zeng; Ya-Rong Xue; Chang-Hong Liu (Fungal Biology, 2026)

Fe-regulated AnMBR for carbon & phosphorus co-recovery and membrane fouling control - Ying Dong; Rong Chen; Jifei Chang; Fengai Yang; Zhen Lei; Xin Wang; Nan Li (Chemical Engineering Journal, 2026)

Mutations in PilZ domains of newly discovered bacterial β-(1,3;1,4)-mixed linkage glucan synthases modulate polysaccharide production - Rebecka Karmakar Saldivar; Shu-Chieh Susie Chang; Sheileza Rajkumari; Rico A. Pratama; Yen-Ting Lin; Mu-Rong Kao; Christina Divne; Chi-Kung Ni; Yves S.Y. Hsieh (Carbohydrate Polymers, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

A wide range of clumped isotope temperatures of Cenozoic island dolostones: Perspectives on dolomite formation - Rong Li; Brian Jones; Chaojin Lu; Biao Chang; Lei Shao (Sedimentary Geology, 2026)

SMART-assisted discovery of scalaranes from the marine sponge Lendenfeldia sp. and its anti-osteoclastogenesis activity - Quoc-Vu Pham; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Lo-Yun Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai; Tsong-Long Hwang (Phytochemistry, 2026)

Sclerohumins G-L: Selective cytotoxic diterpenoids featuring a 4/9-fused ring system from the soft coral Sclerophytum humesi - Phuong Vu Luu; Thuy-Tien Thi Phan; Ngoc-Thac Pham; Huong-Giang Le; Lo-Yun Chen; Huong Lien Ton-Nu; Mei-Hsien Lee; Yao-An Shen; Yu-Jui Fan; Yu-Chia Chang; Jui-Hsin Su; Bo-Rong Peng; et al. (Phytochemistry, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Morphological characteristics, molecular identification, and phylogenetic analysis of the four Leonurus species used for the treatment of gynecological diseases - Qing Du; Ziyi Rong; Yanjuan Guan; Chang Zhang; Liqiang Wang; Xiangyang Zhou; Chuanbei Jiang; Haidong Gao; Bin Wang; Haimei Chen; Chang Liu (Plant Gene, 2026)

PM2.5-modulated targets and miRNAs associated with lung cancer and injury are protected by natural products - Ya-Ting Chuang; Ching-Yu Yen; Wangta Liu; Fang-Rong Chang; Yi-Hong Tsai; Wen-Hsiung Chan; Tsu-Ming Chien; Hsueh-Wei Chang (Environmental Pollution, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

New C22-related terpenoid from Formosan marine sponge Lendenfeldia sp. - Quoc-Vu Pham; Hsin-Wei Wang; Yu-Cheng Chen; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai (Phytochemistry Letters, 2026)

Single and combined impacts of antibiotics on aerobic denitrification: Cell growth characteristics and functional genes expressions - Rong-Rong Chang; Chang-Ze Shi; Yun-Jie Ruan; Bao-Cheng Huang; Ren-Cun Jin; Ming Dong; Wen-Bing Li (Journal of Environmental Sciences, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Effect of freeze–thaw treatment on physicochemical and antioxidant properties of Chinese hawthorn fruit and its juice - Rong Li; Chang Ma; Falong Du; Jiawei Cui; Yunfeng Hu; Junran Chen (Food Chemistry, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Preparation and application of the transistor based on D-A isoindigo copolymer/GR blend for the detection of circular tumor cell - Caiyuan Liao; Fayu Wang; Long Fang; Rong Zou; Yaping Wang; Gang Chang; Hanping He (Analytica Chimica Acta, 2026)

Co-reduction of nitrogen and phosphorus fertilizer inputs reduced nutrient losses and maintained crop yield in a rice-oilseed rape rotation system - Haodong Zhang; Ning Su; Gongwen Luo; Zhi Peng; Xizhe Luo; Sihai Qin; Mengjiao Huang; Chang Tian; Xiangmin Rong; Guixian Xie; Jun Xie (Soil and Tillage Research, 2026)

Metallogenic constraints of sandstone-hosted uranium deposits in arid red beds: A case study from the northwestern Santanghu Basin - Hui Rong; Jun Zhou; Yu Zhou; Yuchen Zhang; Min Liu; Kaiyu Chang (Journal of Geochemical Exploration, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

The effect of rare earth elements (REEs) on plant growth promotion: a review on mechanisms and the role of REE-dependent methylotrophs - Chang-Dong Liu; Jia-Chen Zhao; Wen-Shen Liu; Antony van der Ent; Rong-Liang Qiu; Jean Louis Morel; Ye-Tao Tang (Plant and Soil, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

One new aryltetralin lignan and other components from Blachia pentzii - Yan-Yan Zhang; Feng-Cheng Zhang; Yue Zhang; Hong-Yan Yu; Hai-Rong Xu; Xiao-Yun Dong; Chang-Shui Yang (Phytochemistry Letters, 2025)

Greenhouse gas emissions from field-scale surface-flow constructed wetlands fed with different polluted water types: Environmental and microbial drivers - Deshou Cun; Xiaowan Chen; Junjun Chang; Yang Li; Rong Wu; Rufeng Lin; Shengjiong Deng; Erik Jeppesen; Changqun Duan (Journal of Hydrology, 2025)

Acoustic emission-based damage assessment and failure mechanism analysis on CFST columns with different joint configurations under compression-bending loads - Enchao Rong; Junfu He; Liqiang Tang; Kaizhong Xie; Yanjun Chang (Engineering Structures, 2025)

Chameleon-inspired cellulose photonic gels toward multi-mode visual sensing and deep learning enhanced information encryption - Mengqing Luo; Jinrong Huang; Yun Wu; Qianyao Liu; Rong Yuan; Xiaohua Chang; Yutian Zhu (Chemical Engineering Journal, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Correction: Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2025)

Spatiotemporal transition of resting-state brain networks associates with human cognitive abilities - Lv Zhou; Zhengchang Jiang; Zhao Chang; Rong Wang; Ying Wu (Cognitive Neurodynamics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Development of a Phage‐Display Derived Peptide‐Based Colloidal Gold Strip for Rapid Detection of Enterocytozoon hepatopenaei via Spore Wall Protein Interaction - Jia‐rong Xie; Hao Li; Ben Chen; Yan‐chang Fan; Yu‐hao Gong; Liqun Lu (Journal of Fish Diseases, 2025)
Infection by Enterocytozoon hepatopenaei (EHP) leads to stunted or arrested growth in shrimp, causing significant economic losses in shrimp aquaculture. In this study, the spore wall protein EhSW12 was expressed using a prokaryotic expression system. Subsequently, phage display technology was employed to screen for peptides that interact with EhSW12. A rapid detection method was developed that bypasses the laborious procedure of extracting tissue DNA samples. Instead, enzymatic digestion was used to lyse the spore wall protein present in tissue homogenates, thereby enabling direct detection of EhSW12 via antigen colloidal gold rapid test strips and dot blot assays. The colloidal gold test strips, noted for their convenience and rapidity, satisfy the requirements for on‐site testing, while the dot blot method—with its simple operation—is well suited for high‐throughput sample analysis. Both methods were compared with the national standard qPCR assay. Specificity was validated using various shrimp antigens prepared in the laboratory; the results demonstrated that only the EHP antigen yielded a positive reaction, with no cross‐reaction observed with other common shrimp pathogens (e.g., white spot syndrome virus, decapod iridescent virus and highly pathogenic Vibrio ). Sensitivity tests indicated that the minimum detection limits for the test strip and dot blot methods were, respectively, 7 × 10 6 copies and 5.2 × 10 4 copies. In summary, both methods exhibit strong specificity, high sensitivity, rapid detection speed and operational simplicity—characteristics that make them highly suitable for large‐scale on‐site rapid testing.

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

A strain of mycovirus AaVV1 mediates hypovirulence of Alternaria species - Ya Rong Wang; Yi Chen; Chang Xin Li; Xiao Gang Li; Jun Zi Zhu; Jie Zhong (Pesticide Biochemistry and Physiology, 2025)

Anti-acrolein from natural products by regulating miRNAs and targets - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Yi-Hong Tsai; Fang-Rong Chang; Tsu-Ming Chien; Hsueh-Wei Chang (Journal of Hazardous Materials, 2025)

Compartment engineering in yeast: a path to increased biochemical production - Yuyang Wang; Liyan Cao; Lanxin Rong; Chen Ding; Chang Liu; Qingqing Ye; Qingeng Huang; Cui-ying Zhang; Ning Xu; Jiwei Mao; Jee Loon Foo; Aiqun Yu (Chemical Engineering Journal, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

An innovative bioactive ingredient preparation method without column chromatography and gel filtration: High-purity 3S,3'S- astaxanthin from bioresources - Wei-Cheng Yuan; Tung-Ying Wu; Pei-Yi Chu; Fang-Rong Chang; Yang-Chang Wu (Phytochemistry Letters, 2025)

Chemical composition and bioactivity of Uvaria micrantha from Vietnam - Fang-Rong Chang; Hao-Chun Hu; Szu-Yin Yu; Yi-Hong Tai; Hsin-Yi Tang (Phytochemistry Letters, 2025)

Exploring on the networking of chemical compositions and their cytotoxicity toward KBCC Nepenthes plants - Szu-Yin Yu; Hao-Chun Hu; Attila Hunyadi; Fang-Rong Chang (Phytochemistry Letters, 2025)

Phytochemical analysis and quality control study of Dendrobium fimbriatum Hook. Flowers - Anham Abbasi; Yuan-Shiun Chang; Wu-Chang Chuang; Hung-Rong Yen; Michael Heinrich; Chia-Lin Lee (Phytochemistry Letters, 2025)

A steroid-rich fraction from parasitic climber Cocculus hirsutus (L.) W.Theob inhibits coronavirus disease and neutrophilic inflammation - Vidya Febrasca Tenderly; Thiyagarajan Raviraj; Yen Chi Loo; Olha Mykhailenko; Marcela Safratova; Stefan Kosturko; Mahendra Jadhao; Yu-Li Chen; Tsong-Long Hwang; Fang-Rong Chang; Michal Korinek (Phytochemistry Letters, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Neuroprotective Effects, Mechanisms of Action and Therapeutic Potential of the Kv7/KCNQ Channel Opener QO-83 in Ischemic Stroke - Huiran Zhang; Yanfei Tian; Yan Zhang; Yan Wang; Jinlong Qi; Xiangyu Wang; Yi Yuan; Rong Chen; Yupeng Zhao; Chang Liu; Najing Zhou; Lanxin Liu; et al. (Translational Stroke Research, 2025)

OsR126 IncRNA integrates AtWRKY46 and AtEM1 into ABA signaling in Arabidopsis - Lingyun Chang; Shengyi Liu; Nan Zhang; Dongxu Yang; Ziguang Liu; Hongli Yuan; Rong Yan; Xingguo Lan; Yasushi Yukawa; Juan Wu (Plant Cell Reports, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Aircraft Observations of Ice-Phase Microphysical Characteristics in Stratiform Clouds over the Qilian Mountains in Northwestern China - Yuyan Long; Tuanjie Hou; Baojun Chen; Shuangxi Fu; Rong Zhang; Shaofeng Hua; Yi Chang; Boyue Zhang (Advances in Atmospheric Sciences, 2025)

Anaerobic membrane distillation bioreactors for saline organic wastewater treatment: Impacts of salt accumulation on methanogenesis and microbial community - Zhimeng Yang; Linjiang Jiang; Haiyang Yang; Haiqing Chang; Yuxuan Wan; Huarong Yu; Hongwei Rong; Fangshu Qu (Water Research, 2025)

3,4-seco-Prenyllabdane sesterterpenoids and 3,4-seco-labdane diterpenoids with Zika virus inhibitory potential from Callicarpa nudiflora - Xue-Wen Wu; Guan-Rong Qiao; Xue-Rong Zhao; Qi Li; Muhammad Aurang Zeb; Xiao-Li Li; Chang-Bo Zheng; Wei-Lie Xiao (Phytochemistry, 2025)

Regulatory measures for mitigating physical and mental health impacts in aerospace environment: A systematic review - Rong Liang; Jing Gao; Xiaohui Liu; Xinyao Li; Haonan Chang; Rongdian Yang; Jiajia Yang; Dong Ming (Life Sciences in Space Research, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Novel carbonylomics with stable isotope-coded derivatization for non-targeted analysis of reactive carbonyl species in cooking oils - Chiung-Wen Hu; Yuan-Jhe Chang; Yi-Jhen Wang; Yet-Ran Chen; Marcus S. Cooke; Mu-Rong Chao (Journal of Hazardous Materials, 2025)

Antibiotics shape the core microbial community distribution between floc and biofilm in an endogenous partial denitrification system: Insight from metabolic pathway - Kai-Yue Dong; Chao-Xi Yang; Jin-Luo Pang; Rong-Rong Chang; Ke-Yu Chen; Wei Yao; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Combining soy protein isolate and sorbitol as cryoprotectants for portuguese oysters (Crassostrea angulata) and investigating the effect on ice crystal damage - Chao-Kai Chang; Yi-Feng Kao; Huey-Jine Chai; Pei-Rong Liang; Wei-Lun Zhu; Kai Shyu; Ratna Sari Listyaningrum; Chang-Wei Hsieh (Food Chemistry, 2025)

A novel tin dioxide field effect transistor with PMMAA functionalized organic passivation layer for the detection of the cortisol in saliva - Caiyuan Liao; Rong Zou; Qixin Zhou; Huan-Yu Liu; Song-Mei Liu; Long Fang; Gang Chang; Hanping He (Chemical Engineering Journal, 2025)

Kinetics and morphology study of hydrate formation from CO2-H2O emulsion in glass beads - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Dan Rao; Yu Liu; De-Jun Xuan; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Toxicity evaluation and prioritization of recycled plastic food contact materials using in silico tools - Rachelle D. Arcega; Pei-Shan Chih; Pei-Chun Hsu; Wei-Hsiang Chang; Rong-Jane Chen; Trias Mahmudiono; Ching-Chang Lee; Hsiu-Ling Chen (Journal of Hazardous Materials, 2025)

A chondroinductive peptide sustained-release platform design for cartilage regeneration after microfracture based on novel biomimetic recombinant protein film - Yukun Du; Yinhuan Xia; Shuang Wang; Jianyi Li; Guodong Zhang; Shuqing Chen; Xiaofan Du; Chongmin Ren; Rong-Chang Zeng; Yongming Xi; Weizhi Liu (Chemical Engineering Journal, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Innovating Taiwan's greenhouse gas estimation: A case study of atmospheric methane using GeoAI-Based ensemble mixed spatial prediction model - Hao-Ting Chang; Yinq-Rong Chern; Aji Kusumaning Asri; Wan-Yu Liu; Chin-Yu Hsu; Ta-Chih Hsiao; Kai Hsien Chi; Shih-Chun Candice Lung; Chih-Da Wu (Journal of Environmental Management, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Polyphenolic compounds mitigate the oxidative damage of anammox sludge under long-term light irradiation - Zhi-Qi Ren; Rong-Rong Chang; Hao Wang; Gui-Feng Li; Bao-Cheng Huang; Ren-Cun Jin (Bioresource Technology, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Interfacial modification in multilayered charge generation layer structure for highly efficient charge generation in tandem OLEDs - Nurul Ridho Al Amin; Cheng-Yung Ho; Dun-Cheng Huang; Rong-Miao Chang; Ya-Hsin Cheng; Chih-Hao Chang (Chemical Engineering Journal, 2025)

Transcriptomic Signature of Lipid Production in Australian Aurantiochytrium sp. TC20 - Kim Jye Lee Chang; Eduardo Gorron Gomez; Esmaeil Ebrahimie; Manijeh Mohammadi Dehcheshmeh; Dion M. F. Frampton; Xue-Rong Zhou (Marine Biotechnology, 2025)
Aurantiochytrium not only excels in producing long-chain polyunsaturated fatty acids such as docosahexaenoic acid for humans, but it is also a source of essential fatty acids with minimal impacts on wild fisheries and is vital in the transfer of atmospheric carbon to oceanic carbon sinks and cycles. This study aims to unveil the systems biology of lipid production in the Australian Aurantiochytrium sp. TC20 by comparing the transcriptomic profiles under optimal growth conditions with increased fatty acid production from the early (Day 1) to late exponential growth phase (Day 3). Particular attention was paid to 227 manually annotated genes involved in lipid metabolism, such as FAS (fatty acid synthetase) and subunits of polyunsaturated fatty acids ( PUFA ) synthase. PCA analysis showed that differentially expressed genes, related to lipid metabolism, efficiently discriminated Day 3 samples from Day 1, highlighting the key robustness of the developed lipid-biosynthesis signature. Highly significant (pFDR < 0.01) upregulation of polyunsaturated fatty acid synthase subunit B ( PFAB ) involved in fatty acid synthesis, lipid droplet protein ( TLDP ) involved in TAG-synthesis, and phosphoglycerate mutase ( PGAM-2 ) involved in glycolysis and gluconeogenesis were observed. KEGG enrichment analysis highlighted significant enrichment of the biosynthesis of unsaturated fatty acids (pFDR < 0.01) and carbon metabolism pathways (pFDR < 0.01). This study provides a comprehensive overview of the transcriptional landscape of Australian Aurantiochytrium sp. TC20 in the process of fatty acid production.

Knowledge-based phosphorus input levels control the link between soil microbial diversity and ecosystem functions in paddy fields - Qiaorong Li; Yao Liu; Ning Su; Chang Tian; Yuping Zhang; Lin Tan; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Agriculture, Ecosystems & Environment, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

A new approach to high conversion CO2 hydrate sequestration by CO2/water emulsion injection into marine sediments - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Liang-Liang Ren; Ming Wang; Dan Rao; Yong-Quan Liu; Yi-Bo Hao; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Enriching bottom acceptors for high-performance inkjet-printed organic solar cells - Xingze Chen; Lifeng Sang; Yuanyuan Jiang; Yiyu Chen; Qing Zhang; Rong Huang; Fengqi Guo; Guanghao Lu; Xiaozhang Zhu; Qi Chen; Chang-Qi Ma; Qun Luo (Chemical Engineering Journal, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

Research on an adaptive prediction method for restaurant air quality based on occupancy detection - Yu Zhao; Chang Xiong; Li Rong; Zhiwen Luo; Tareq Hussein; Tianyi Zhao (Building and Environment, 2025)

Diurnal variations in greenhouse gas diffusive emissions from a river covered with submerged macrophytes: environmental and biotic driving factors - Haoyu Wang; Rong Wu; Deshou Cun; Yi Zhang; Yukun Hou; Junjun Chang (Aquatic Sciences, 2025)

New data on the Cambrian–Ordovician (Tremadocian) conodont biostratigraphy of Guizhou Province, Southwest China - Hadi Jahangir; Guan-Zhou Yan; Rong-Chang Wu; Ren-Bin Zhan (Palaeoworld, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Integrative transcriptomic analysis reveals a broad range of toxic effects of triclosan on coral Porites lutea - Hao Liang; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Rong-Gui Zhu; Chao-Yang Zhou; Zhen-Zhu Liu; Kefu Yu (Journal of Hazardous Materials, 2024)

Evolution and health risk of indicator microorganisms in landscape water replenished by reclaimed water - Yitong Chen; Chang Qi; Yanan Yu; Xiaoxin Cao; Xiang Zheng; Rong Cheng (Journal of Environmental Sciences, 2024)

Enhanced remediation of real agricultural runoff in surface-flow constructed wetlands by coupling composite substrate-packed bio-balls, submerged plants and functional bacteria: Performance and mechanisms - Shengjiong Deng; Deshou Cun; Rufeng Lin; Dongliang Peng; Yanduo Du; Aoxue Wang; Bowen Guan; Rong Tan; Junjun Chang (Environmental Research, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The effect of Desulfovibrio caledoniensis and Pseudomonas aeruginosa on the corrosion behaviour of 70Cu-30Ni alloy - Li-Jun He; Zheng-Hui Qiu; Shao-Xia Ma; Rong-Chang Zeng; Cun-Guo Lin (Biofouling, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Polymerizable deep eutectic solvent enables flexible gel formation for motion sensor and anti-UV film - Shanlei Chang; Kai Rong; Yuchen Wang; Zhixuan Yu; Junfeng Zhai; Hongwei Tian; Youxing Fang; Shaojun Dong (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Effect of the spatial changes in engineering properties on municipal solid waste landfill slope stability - Rong Yang; Zengguang Xu; Junrui Chai; Cheng Cao; Jianxi Ren; Xiaoke Chang (Bulletin of Engineering Geology and the Environment, 2024)

A potential trade-off between reproduction and enhancement of thermotolerance in Liriomyza trifolii populations driven by thermal acclimation - Yu-Cheng Wang; Ya-Wen Chang; Fei Yang; Wei-Rong Gong; Jie Hu; Yu-Zhou Du (Journal of Thermal Biology, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Two glycosyl transferase 2 genes from the gram-positive bacterium Clostridium ventriculi encode (1,3;1,4)-β-D-glucan synthases - Shu-Chieh Chang; Rebecka Karmakar Saldivar; Mu-Rong Kao; Xiaohui Xing; Chun-Hong Yeh; Jiun-Jie Shie; D. Wade Abbott; Philip J. Harris; Yves S.Y. Hsieh (Carbohydrate Polymers, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Numerical Analysis of Leading-Edge Roughness Effects on the Aerodynamic Performance of a Thick Wind Turbine Airfoil - Wei Zhang; Kuichao Ma; Chang Cai; Xiangyu Sun; Jun Zhang; Xiaohui Zhong; Xiaomin Rong; Qing’an Li (Journal of Marine Science and Engineering, 2024)
The aerodynamic performance of wind turbine airfoils is crucial for the efficiency and reliability of wind energy systems, with leading-edge roughness significantly impacting blade performance. This study conducts numerical simulations on the DU 00-W-401 airfoil to investigate the effects of leading-edge roughness. Results reveal that the rough airfoil exhibits a distinctive “N”-shaped lift coefficient curve. The formation mechanism of this nonlinear lift curve is primarily attributed to the development of the trailing-edge separation vortex and variations in the adverse pressure gradient from the maximum thickness position to the trailing-edge confluence. The impact of different roughness heights is further investigated. It is discovered that when the roughness height is higher than 0.3 mm, the boundary layer can be considered fully turbulent, and the lift curve shows the “N” shape stably. When the roughness height is between 0.07 mm and 0.1 mm, a transitional state can be observed, with several saltation points in the lift curve. The main characteristics of different flow regimes based on different lift curve segments are summarized. This research enhances the understanding of the effects of leading-edge roughness on the aerodynamic performance of a thick wind turbine airfoil, and the simulation method for considering the effect of leading-edge roughness is practical to be applied on large-scale wind turbine blade to estimate the aerodynamic performance under rough leading-edge conditions, thereby supporting advancements in wind turbine technology and promoting the broader adoption of renewable energy.

Microbial and hydrothermal dolomite formation in Early Cretaceous lacustrine sediments in Yin'e Basin: Insights from petrology and geochemistry - Kun Zhang; Ziping Liu; Zhitao Xu; Qing Chang; Douaa Fathy; Rong Liu; Edith Bai (Sedimentary Geology, 2024)

Construction of large-aperture mesoporous silica spheres supported polyoxometalate heterogeneous catalysts and their high-efficiency for the ultra-deep desulfurization - Jia-Qi Wu; Lu-lu Ma; Zhuang-Zhuang Li; Xin Li; Si-Wen Li; Chang Li; Rong-Xi Li; Jian-She Zhao (Fuel, 2024)

Rapid adsorptive removal of emerging and legacy per- and polyfluoroalkyl substances (PFASs) from water using zinc chloride-modified litchi seed-derived biochar - Zhen-Zhu Liu; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Hong-Ming Tan; Rong-Gui Zhu; Chao-Yang Zhou; Hao Liang; Kefu Yu (Bioresource Technology, 2024)

Experimental Study on Acoustic Emission Properties and Damage Characteristics of Basalt Exposed to High Temperature Treatment - Wenzhao Chen; Rong Hu; Xiqi Liu; Gang Wang; Bingwen Gong; Yan Chang; Heng Deng; Chunming Qi (Geotechnical and Geological Engineering, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

External redox couple enhanced anammox sludge activity at low temperature: Insight into intracellular resource synthesis - Rong-Rong Chang; Wei Yao; Jin-Luo Pang; Kai-Yue Dong; Yao-Yao Lu; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

The role of a novel secretory peptidoglycan recognition protein with antibacterial ability from the Chinese Oak Silkworm Antheraea pernyi in humoral immunity - Xutong Duan; Ting Fu; Chang Liu; Fuhui Wang; Chengbao Liu; Lin Zhao; JinZhu Yu; Xialu Wang; Rong Zhang (Insect Biochemistry and Molecular Biology, 2024)

Marine anticancer drugs in modulating miRNAs and antioxidant signaling - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Kuo-Chuan Wu; Fang-Rong Chang; Yi-Hong Tsai; Tsu-Ming Chien; Hsueh-Wei Chang (Chemico-Biological Interactions, 2024)

Potential Role of Endoplasmic Reticulum Stress in Modulating Protein Homeostasis in Oligodendrocytes to Improve White Matter Injury in Preterm Infants - Chang Liu; Rong Ju (Molecular Neurobiology, 2024)

Novel insights into dimethylsulfoniopropionate cleavage by deep subseafloor fungi - Xuan Liu; Xin-Ran Wang; Fan Zhou; Ya-Rong Xue; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Multiple scenario land use simulation based on a coupled MOGA-PLUS model: a case of the Yellow River Basin - Guanghui Li; Yinghui Chang; Pengyan Zhang; Qianxu Wang; Zhuo Chen; Xinyue Zhang; Guangrui Xing; Rong Lu; Mengfan Li; Lei Gu (Environmental Science and Pollution Research, 2024)

Simultaneous determination of trace marine lipophilic and hydrophilic phycotoxins in various environmental and biota matrices - Chao-Yang Zhou; Chang-Gui Pan; Feng-Jiao Peng; Rong-Gui Zhu; Jun-Jie Hu; Kefu Yu (Marine Pollution Bulletin, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Investigation of graphic carbon nitride supported Ag-modified cobalt oxides for N2O decomposition at low temperature - Yimeng Yin; Rong Xiao; Lei Qiu; Chizhong Wang; Huazhen Chang (Fuel, 2024)

DNA modifications: Biomarkers for the exposome? - Carolina Möller; Jazmine Virzi; Yuan-Jhe Chang; Alexandra Keidel; Mu-Rong Chao; Chiung-Wen Hu; Marcus S. Cooke (Environmental Toxicology and Pharmacology, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Self-assembly of protein-DNA hybrids dedicated to an accelerated and self-primed strand displacement amplification for reinforced serum microRNA probing - Guoqiao Huang; Chan Li; Rong Wu; Guohui Xue; Qiufeng Song; Linwen Lan; Chang Xue; Liang Xu; Zhifa Shen (Analytica Chimica Acta, 2024)

A literature review on phosphate removal from wastewater by lanthanum-based adsorbents: From mechanisms to applications - Yao-Yao Lu; Hao Wang; Rong-Rong Chang; Wen-Bing Li; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

Strain partitioning dominated growth of strike-slip fault: Insight from the Tan-Lu fault in Eastern China - Rong Chu; Dan-Ping Yan; Liang Qiu; De-Shuang Chang; Qi Wang; Xian-Qiang Song; Chao Wang (Journal of Structural Geology, 2024)

Landfill leachate treatment by direct contact membrane distillation: Impacts of landfill age on contaminant removal performance, membrane fouling and scaling - Zhimeng Yang; Songze Lin; Linxiong Ye; Dan Qu; Haiyang Yang; Haiqing Chang; Huarong Yu; Zhongsen Yan; Hongwei Rong; Fangshu Qu (Desalination, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Purine permease (PUP) family gene PUP11 positively regulates the rice seed setting rate by influencing seed development - Chenyu Rong; Renren Zhang; Yuexin Liu; Zhongyuan Chang; Ziyu Liu; Yanfeng Ding; Chengqiang Ding (Plant Cell Reports, 2024)

Cultivation mode of Saccharina japonica impacts planktonic and epiphytic microbiomes - Yongwei Yan; Shanshan Wang; Shaojun Pang; Kuimei Liu; Lirong Chang; Xiaojun Rong; Jie Li (Algal Research, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Inactivation of antibiotic resistant bacteria by Fe3O4 @MoS2 activated persulfate and control of antibiotic resistance dissemination risk - Chang Rong; Haijun Chen; Zhuowen Wang; Shiyi Zhao; Deming Dong; Jiao Qu; Na Zheng; Haiyang Liu; Xiuyi Hua (Journal of Hazardous Materials, 2024)

A novel method for in situ imaging of root exudates and labile elements reveals phosphorus deficiency-induced mobilization of rare earth elements in the rhizosphere of Phytolacca americana - Chong Liu; Ting-Xuan Ding; Antony van der Ent; Chang Liu; Jean Louis Morel; Catherine Sirguey; Wen-Shen Liu; Ye-Tao Tang; Rong-Liang Qiu (Plant and Soil, 2024)

Parabens and their metabolite in a marine benthic-dominated food web from the Beibu gulf, South China Sea: Occurrence, trophic transfer and health risk assessment - Rong-Gui Zhu; Chang-Gui Pan; Feng-Jiao Peng; Chao-Yang Zhou; Jun-Jie Hu; Kefu Yu (Water Research, 2024)

An updated review of the genus Rhododendron since 2010: Traditional uses, phytochemistry, and pharmacology - Xing-Jian Liu; Hai-Guo Su; Xing-Rong Peng; Hui-Chang Bi; Ming-Hua Qiu (Phytochemistry, 2024)

An appropriate amount of straw replaced chemical fertilizers returning reduced net greenhouse gas emissions and improved net ecological economic benefits - Lian Zhang; Guoliang Jiang; Rusheng Xiao; Kun Hou; Xin Liu; Xinyu Liu; Pei Yuan; Feng Tian; Lichu Yin; Hongmei Zhu; Chang Tian; Lan Yang; et al. (Journal of Cleaner Production, 2024)

Normal fault evolution in the Penghu Basin, a Paleogene Rift Basin in Western Taiwan Strait: A test of fault growth models - Pin-Rong Wu; Kenn-Ming Yang; Pin-Chi Wang; Chang-Jie Lee; Jong-Chang Wu (Tectonophysics, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Metabonomics analysis of microalga Scenedesmus obliquus under ciprofloxacin stress - Yue Wang; Weihao Ning; Shengnan Li; Changfei Gao; Rong Cui; Wanqian Guo; Jo-Shu Chang; Shih-Hsin Ho (Environmental Research, 2023)

Recent advances in nanofiltration-based hybrid processes - Tian-Zhi Jia; Ming-Yue Rong; Chang-Tao Chen; Wai Fen Yong; Siew Kei Lau; Rong-Fei Zhou; Min Chen; Shi-Peng Sun (Desalination, 2023)

Adaptability law of central heating environment under the effect of thermal history: A continuous field survey - Chao Jia; Xihao Bie; Chang Sun; Zhicheng Zhang; Yonghua Rong; Jing Cao; Menghan Wang (Building and Environment, 2023)

Crop residue retention increases greenhouse gas emissions but reduces chemical fertilizer requirement in a vegetable-rice rotation - Le Qi; Prem Pokharel; Rong Huang; Scott X. Chang; Xiaoqiang Gong; Tao Sun; Yueqiang Wu; Zifang Wang; Ming Gao (Agricultural and Forest Meteorology, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Emergence of the clinical rdar morphotype carbapenem-resistant and hypervirulent Klebsiella pneumoniae with enhanced adaption to hospital environment - Congcong Liu; Ning Dong; Xueting Huang; Zixian Huang; Chang Cai; Jiayue Lu; Hongwei Zhou; Jingren Zhang; Yu Zeng; Fan Yang; Gongxiang Chen; Zhangqi Shen; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Simultaneous removal of sulfamethoxazole during fermentative production of short-chain fatty acids - Yue Wang; Rongrong Lin; Yushuang Cao; Shuangfei Li; Rong Cui; Wanqian Guo; Shih-Hsin Ho; Yoong Kit Leong; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

In vitro antioxidant, antiglycation, α-glucosidase and α-amylase inhibitory activities of extracts and solvent fractions of Elaeocarpus serratus L. - Zakhele Mphatsi Dlamini; Chiy-Rong Chen; Bongani Sicelo Dlamini; Chi-I Chang (Biocatalysis and Agricultural Biotechnology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Land use regulates the spectroscopic properties and sources of dissolved organic matter in the inflowing rivers of a large plateau lake in southwestern China: implication for organic pollution control - Rong Wu; Weijie Guo; Yutong Li; Shengjiong Deng; Junjun Chang (Environmental Science and Pollution Research, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

A 3D phytic acid cross-linked high-porous conductive hydrogel integrating g-C3N4 for electrochemical multiplex sensing of heavy metal ions - Lu Xiao; Yulan Zhao; Gang Chang; Huiling Yan; Rong Zou; Xiuhua Zhang; Shengfu Wang; Hanping He (Analytica Chimica Acta, 2023)

Nε-(1-Carboxymethyl)-L-lysine, an advanced glycation end product, exerts malignancy on chondrosarcoma via the activation of cancer stemness - Ting-Yu Chang; Kuo-Cheng Lan; Chia-Hung Wu; Meei-Ling Sheu; Rong-Sen Yang; Shing-Hwa Liu (Archives of Toxicology, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Biome responses to a hydroclimatic crisis in an Early Cretaceous (Barremian–Aptian) subtropical inland lake ecosystem, Northwest China - Kun Zhang; Rong Liu; Edith Bai; Zibin Zhao; Giovan Peyrotty; Douaa Fathy; Qing Chang; Ziping Liu; Kai Yang; Chuan Xu; Zhaojun Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Conodont biostratigraphy and carbon isotope chemostratigraphy of the Middle to Upper Ordovician on the western Yangtze Platform, South China - Fang-Yi Gong; Guan-Zhou Yan; Rong-Chang Wu (Palaeoworld, 2023)

Development of heterogenous electro-Fenton process with immobilized FeWO4 catalyst for the degradation of tetracycline and the treatment of crude oil tank cleaning wastewater in neutral medium - Yanyang Chu; Chang Liu; Rong Wang; He Chen (Chemical Engineering Journal, 2023)

An endogenous neuropeptide hormone assists cancer cells in escaping from immune surveillance - Chang-Yu Yan; Yan-Ping Wu; Yi-Fang Li; Rong-Rong He (Science China Life Sciences, 2023)

Molecular characterization and antimicrobial activity of NK-lysin in black scraper (Thamnaconus modestus) - Mei-Yi Liu; Yi-Rong Zhang; Jian-Hua Zhang; Liang Miao; Yun-Fei Dang; Chen-Jie Fei; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Amycolatolides A and B: Two new secondary metabolites from the lichen-derived actinomycete Amycolatopsis sp. YIM 130923 - Qing-Rong Yang; Yi Jiang; Chuan-Sheng Liu; Tang-Chang Xu; Rong Huang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Social environments still matter: The role of physical and social environments in place attachment in a transitional city, Guangzhou, China - Jiang Chang; Zihan Lin; Igor Vojnovic; Jiaguo Qi; Rong Wu; Dixiang Xie (Landscape and Urban Planning, 2023)

Preparation of lotus-leaf-like carbon cathode for the electro-Fenton oxidation process: Hydrogen peroxide production, various organics degradation and printing wastewater treatment - Chang Liu; Yanyang Chu; Rong Wang; Jinruo Fan (Journal of Water Process Engineering, 2023)

Visible-light-driven photocatalytic degradation of tetracycline hydrochloride by Z-scheme Ag3PO4/1T@2H-MoS2 heterojunction: Degradation mechanism, toxicity assessment, and potential applications - Xiuyi Hua; Haijun Chen; Chang Rong; Francis Addison; Deming Dong; Jiao Qu; Dapeng Liang; Zhiyong Guo; Na Zheng; Haiyang Liu (Journal of Hazardous Materials, 2023)

Episodic magmatism in the Dananhu arc, eastern Tianshan: Implications for the Late Palaeozoic tectonic evolution of the North Tianshan Ocean - Rong-Song Tian; M.N. Muhtar; Guo-Ai Xie; Chang-Zhi Wu (International Geology Review, 2023)

Genome-wide DNA methylation and transcription analysis reveal the potential epigenetic mechanism of heat stress response in the sea cucumber Apostichopus japonicus - Mengyang Chang; Jianlong Ge; Meijie Liao; Xiaojun Rong; Yingeng Wang; Bin Li; Xinrong Li; Jinjin Wang; Zheng Zhang; Yongxiang Yu; Chunyuan Wang (Frontiers in Marine Science, 2023)
DNA methylation is an important epigenetic modification that regulates many biological processes. The sea cucumber Apostichopus japonicus often suffers from heat stress that affects its growth and leads to significant economic losses. In this study, the mRNA expression patterns and DNA methylation characteristics in the body wall of A. japonicus under heat stress were analyzed by whole-genome bisulfite sequencing (WGBS) and transcriptome sequencing (RNA-seq). We found that CpG was the main DNA methylation type, and heat stress caused a significant increase in the overall methylation level and methylation rate, especially in the intergenic region of the A. japonicus genome. In total, 1,409 differentially expressed genes (DEGs) and 17,927 differentially methylated genes (DMGs) were obtained by RNA-seq and WGBS, respectively. Association analysis between DNA methylation and transcription identified 569 negatively correlated genes in both DMGs and DEGs, which indicated that DNA methylation affects on transcriptional regulation in response to heat stress. These negatively correlated genes were significantly enriched in pathways related to energy metabolism and immunoregulation, such as the thyroid hormone signaling pathway, renin secretion, notch signaling pathway and microRNAs in cancer. In addition, potential key genes, including heat shock protein ( hsp70 ), calcium-activated chloride channel regulator 1( clca1 ), and tenascin R ( tnr ), were obtained and their expression and methylation were preliminarily verified. The results provide a new perspective for epigenetic and transcriptomic studies of A. japonicus response to heat stress, and provide a reference for breeding sea cucumbers resistant to high temperatures.

The effectiveness of eight-years phosphorus reducing inputs on double cropping paddy: Insights into productivity and soil-plant phosphorus trade-off - Ning Su; Guixian Xie; Zhiwei Mao; Qiaorong Li; Tian Chang; Yuping Zhang; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Science of The Total Environment, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Toxicity prediction: An application of alternative testing and computational toxicology in contaminated groundwater sites in Taiwan - Rachelle D. Arcega; Rong-Jane Chen; Pei-Shan Chih; Yi-Hsuan Huang; Wei-Hsiang Chang; Ting-Khai Kong; Ching-Chang Lee; Trias Mahmudiono; Chun-Chih Tsui; Wen-Che Hou; Hsin-Ta Hsueh; Hsiu-Ling Chen (Journal of Environmental Management, 2023)

Environmental Factors Influence the Effects of Biochar on the Bioavailability of Cd and Pb in Soil Under Flooding Condition - Honghong Li; Zhou Li; Limei Huang; Xiaoming Mao; Yuxuan Dong; Shilong Fu; Rong Su; Yihan Chang; Chuan Zhang (Water, Air, & Soil Pollution, 2023)

Selectivity of natural isoquinoline alkaloid assembler in programming poly(dA) into parallel duplex by polyvalent synergy - Shuzhen Peng; Yun Chang; Xingli Zeng; Rong Lai; Mujing Yang; Dandan Wang; Xiaoshun Zhou; Yong Shao (Analytica Chimica Acta, 2023)

Crop rotation-driven change in physicochemical properties regulates microbial diversity, dominant components, and community complexity in paddy soils - Hanfeng Zhang; Gongwen Luo; Yizhe Wang; Jiangchi Fei; Rong Xiangmin; Jianwei Peng; Chang Tian; Yuping Zhang (Agriculture, Ecosystems & Environment, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Nucleic acid adductomics – The next generation of adductomics towards assessing environmental health risks - Marcus S. Cooke; Yuan-Jhe Chang; Yet-Ran Chen; Chiung-Wen Hu; Mu-Rong Chao (Science of The Total Environment, 2023)

An approach to the high efficient exploitation of nature gas hydrate and carbon sequestration via injecting CO2/H2 gas mixture with varying composition - Bo-Jian Cao; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Ming-Long Wang; Meng-Ya Niu; Jing-Yu Kan; Chang-Yu Sun; Dao-Yi Chen; Guang-Jin Chen (Chemical Engineering Journal, 2023)

Performance and Feasibility of Therapeutic Vibrating Mesh Nebulizer for Ventilation Lung Scan - Chih-Yung Chang; Bang-Hung Yang; Chien-Chih Ke; Jing-Long Hsu; Rong-Hong Jhou; Wen-Yi Chang; Nan-Jing Peng; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2022)

Insights into the α-amylase and α-glucosidase inhibition mechanism of 4-(4-hydroxyphenyl)-but-3-en-2-one from Scutellaria barbata D. Don: enzymatic kinetics, fluorescence spectroscopy and computational simulation - Bongani S. Dlamini; Chiy-Rong Chen; Wen-Ling Shih; Yu-Kuo Chen; Jue-Liang Hsu; Chi-I Chang (Medicinal Chemistry Research, 2022)

Adsorption properties and mechanism of ginkgo biloba leaf-based materials for Cd (II) in aqueous solution - Yan-rong Cai; Yang Song; Chun Chang (Environmental Science and Pollution Research, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Sequencing and comparative analysis of chloroplast genomes of three medicinal plants: Gentiana manshurica, G. scabra and G. triflora - Rong Zhao; Shuyue Yin; Jianing Xue; Chang Liu; Yanping Xing; Haibo Yin; Xue Ren; Jixiang Chen; Dingding Jia (Physiology and Molecular Biology of Plants, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Mapping quantitative trait loci underlying drought-related traits in rice using a doubled-haploid population - Phichitra Wongchuwech; Rong-Kuen Chen; Yueh-Long Chang (Cereal Research Communications, 2022)

Neiella holothuriorum sp. nov., isolated from the gut of a sea cucumber Apostichopus japonicus - Xin-Feng Bai; Xue-Lian Lv; Xue Liu; Ting-Ting Cui; Mian-Song Zhang; Ning Ding; Chang-Heng Liu; Ai-Rong Jia (Antonie van Leeuwenhoek, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

MiR-196a promotes the proliferation and migration of esophageal cancer via the UHRF2/TET2 axis - Chang-mei Hu; Jie Peng; Liang Lv; Xue-hong Wang; Ji-rong Huo; De-liang Liu (Molecular and Cellular Biochemistry, 2022)

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Serum- and Feeder-Free Culture of Juvenile Monkey Female Germline Stem Cells and Testosterone Regulation of their Self-Renewal - Xiaoyong Li; Xiaoying Yao; Chunlan Mu; Zhaoxia Wang; Rong Hu; Yan Chang; Ji Wu (Stem Cell Reviews and Reports, 2022)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Effect of oxygen concentrations and branched‐chain amino acids on the growth and development of sub‐seafloor fungus, Schizophyllum commune 20R‐7‐F01 - Muhammad Zain Ul Arifeen; Zhi‐Jun Ma; Si Wu; Jun‐Zhong Liu; Ya‐Rong Xue; Chang‐Hong Liu (Environmental Microbiology, 2021)
Summary Fungi have been reported to be the dominant eukaryotic group in anoxic sub‐seafloor sediments, but how fungi subsist in the anoxic sub‐marine sedimental environment is rarely understood. Our previous study demonstrated that the fungus, Schizophyllum commune 20R‐7‐F01 isolated from a ~2 km sediment below the seafloor, can grow and produce primordia in the complete absence of oxygen with enhanced production of branched‐chain amino acids (BCAAs), but the primordia cannot be developed into fruit bodies without oxygen. Here, we present the individual and synergistic effects of oxygen and BCAAs on the fruit‐body development of this strain. It was found that the fungus required a minimum oxygen concentration of 0.5% pO 2 to generate primordia and 1% pO 2 to convert primordia into mature fruit body. However, if BCAAs (20 mM) were added to the medium, the primordium could be developed into fruit body at a lower oxygen concentration up to 0.5% pO 2 where genes fst4 and c2h2 playing an important role in compensating oxygen deficiency. Moreover, under hypoxic conditions, the fungus showed an increase in mitochondrial number and initiation of auto‐phagocytosis. These findings suggest that the fruit‐body formation of S. commune may have multiple mechanisms, including energy and amino acid metabolism in response to oxygen concentrations.

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

Effects of anaerobic digestion of food waste on biogas production and environmental impacts: a review - Kah Rong Chew; Hui Yi Leong; Kuan Shiong Khoo; Dai-Viet N. Vo; Hirra Anjum; Chih-Kai Chang; Pau Loke Show (Environmental Chemistry Letters, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Converting rice husk to biochar reduces bamboo soil N2O emissions under different forms and rates of nitrogen additions - Rong Zhou; Ali El-Naggar; Yongfu Li; Yanjiang Cai; Scott X. Chang (Environmental Science and Pollution Research, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Triaxial Compression Testing at Constant and Reducing Confining Pressure for the Mechanical Characterization of a Specific Type of Sandstone - Jiu-chang Zhang; Zhi-nan Lin; Bo Dong; Rong-xin Guo (Rock Mechanics and Rock Engineering, 2021)

Variation in rare earth element (REE), aluminium (Al) and silicon (Si) accumulation among populations of the hyperaccumulator Dicranopteris linearis in southern China - Wen-Shen Liu; Hong-Xiang Zheng; Chang Liu; Mei-Na Guo; Shi-Chen Zhu; Yue Cao; Rong-Liang Qiu; Jean Louis Morel; Antony van der Ent; Ye-Tao Tang (Plant and Soil, 2021)

Involvement of Mitophagy in Aluminum Oxide Nanoparticle–Induced Impairment of Learning and Memory in Mice - Tao Huang; Weiwei Guo; Yanhong Wang; Lijun Chang; Nan Shang; Jin Chen; Rong Fan; Lan Zhang; Xiaocheng Gao; Qiao Niu; Qinli Zhang (Neurotoxicity Research, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Retraction Note: Fibrauretine reduces ischemia/reperfusion injury via RISK/eNOS activation - Chunsheng Wang; Rong Chang; Gan Gao; Xing Liu; Yingwei Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

A Eu(III)-based Metal Organic Framework: Selective Sensing of Picric Acid and Nursing Application Values On the Cerebral Edema Induced by Cerebral Hemorrhage Via Reducing the Coagulation Factor II Activity - Xiao-Chang Chen; Feng Xi; Rong Liu; Jia-Wen Zhou (Journal of Fluorescence, 2021)

Phytoremediation of Cadmium Contaminated Soil: Impacts on Morphological Traits, Proline Content and Stomata Parameters of Sweet Sorghum Seedlings - Xicun Dong; Yan Chang; Rong Zheng; Xueqiang Wang; Xia Yan; Xiao-Fei Ma (Bulletin of Environmental Contamination and Toxicology, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Controlled-release N fertilizer to mitigate ammonia volatilization from double-cropping rice - Chang Tian; Xuan Zhou; Zheli Ding; Qiang Liu; Guixian Xie; Jianwei Peng; Xiangming Rong; Yuping Zhang; Yong Yang; Mamdouh A. Eissa (Nutrient Cycling in Agroecosystems, 2021)
Controlled-release nitrogen fertilizer (CRNF) can effectively enhance crop yields and raise the efficiency of nitrogen fertilizer in agroecosystems. In the present study, the volatilization of NH 3 was determined by airflow enclosure chamber technique after the application of different CRNF rates in double-cropping rice fields in southern China for continuous 3 years. The early and late season rice (ESR and LSR) were cultivated each year. The results showed that the total NH 3 volatilization losses ranged from 25 to 56 kg N ha −1 in ESR and from 32 to 61 kg N ha −1 in LSR. The loss of N to the total applied N ranged from 12 to 29% in ESR and from 12 to 27% in LSR. The application of CRNF significantly reduced the cumulative NH 3 volatilization losses by 20–43% for ESR and by 20–32% for LSR compared with conventional urea application. CRNF in LSR was less effective to reduce NH 3 volatilization than that in ESR. Furthermore, the application of 80% of N rate in the form of CRNF gave higher grain yield and apparent nitrogen recovery efficiency (ANRE) than that of application of 100% of N rate from conventional urea. CRNF can effectively reduce NH 3 volatilization, and increase rice yield and ANRE. Considering higher price of CRNF, the application of CRNF at lower (20% applied N) rate than conventional urea in LSR may be a reasonable fertilization strategy for improving N use efficiency, environment effectiveness, and sustaining the development of rice production systems in double-cropping rice.

Prenatal Stress Leads to the Altered Maturation of Corticostriatal Synaptic Plasticity and Related Behavioral Impairments Through Epigenetic Modifications of Dopamine D2 Receptor in Mice - Yingchun Li; Jing Rong; Haiquan Zhong; Min Liang; Chunting Zhu; Fei Chang; Rong Zhou (Molecular Neurobiology, 2021)

Heavy metal concentrations and associated health risks in edible tissues of marine nekton from the outer Pearl River Estuary, South China Sea - Chang-Ping Yang; Yan Liu; Bin-Bin Shan; Jing Xu; Wei Yu; Dian-Rong Sun; Zai-Wang Zhang (Environmental Science and Pollution Research, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Natural products development under epigenetic modulation in fungi - Chi-Ying Li; Yu-Ming Chung; Yang-Chang Wu; Attila Hunyadi; Clay C. C. Wang; Fang-Rong Chang (Phytochemistry Reviews, 2020)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Correction of seismic attribute-based small-structure prediction errors using GPR data—A case study of the Shuguang Coal Mine, Shanxi - Cui Fan; Zhao Zhi-Rong; Du Yun-Fei; Bai Yu; Xu Chang-Qing; Jia Xiao-Feng (Applied Geophysics, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

RETRACTED ARTICLE: Fibrauretine reduces ischemia/reperfusion injury via RISK/eNOS activation - Chunsheng Wang; Rong Chang; Gan Gao; Xing Liu; Yingwei Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Microalgae for saline wastewater treatment: a critical review - Hoang Nhat Phong Vo; Huu Hao Ngo; Wenshan Guo; Soon Woong Chang; Dinh Duc Nguyen; Zhuo Chen; Xiaochang C. Wang; Rong Chen; Xinbo Zhang (Critical Reviews in Environmental Science and Technology, 2020)

Functional characterization of a low-frequency V1937I variant in FASN associated with susceptibility to esophageal squamous cell carcinoma - Xiaoyang Wang; Jianbo Tian; Qianyu Zhao; Nan Yang; Pingting Ying; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Ying Gao; Jiang Chang; Xiaoping Miao (Archives of Toxicology, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Polymer-coated urea effects on maize yield and nitrogen losses for hilly land of southern China - Yong Xie; Li Tang; Lan Yang; Yuping Zhang; Haixing Song; Chang Tian; Xiangmin Rong; Yongliang Han (Nutrient Cycling in Agroecosystems, 2020)

Reduced mineral fertilization coupled with straw return in field mesocosm vegetable cultivation helps to coordinate greenhouse gas emissions and vegetable production - Rong Huang; Jiang Liu; Xinhua He; Deti Xie; Jiupai Ni; Chang Xu; Yarong Zhang; En Ci; Zifang Wang; Ming Gao (Journal of Soils and Sediments, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

Three functional variants were identified to affect RPS24 expression and significantly associated with risk of colorectal cancer - Danyi Zou; Hongli Zhang; Juntao Ke; Jiaoyuan Li; Ying Zhu; Yajie Gong; Yang Yang; Jianbo Tian; Yi Zhang; Xiating Peng; Kailin Cai; Rong Zhong; et al. (Archives of Toxicology, 2020)

Reverting Metabolic Dysfunction in Cortex and Cerebellum of APP/PS1 Mice, a Model for Alzheimer’s Disease by Pioglitazone, a Peroxisome Proliferator-Activated Receptor Gamma (PPARγ) Agonist - Kai Lun Chang; Ling Rong Wong; Hai Ning Pee; Shili Yang; Paul Chi-Lui Ho (Molecular Neurobiology, 2019)

Hyperinsulinemia-induced KLF5 mediates endothelial angiogenic dysfunction in diabetic endothelial cells - Xi-hui Wang; Chang-you Yan; Jian-rong Liu (Journal of Molecular Histology, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Co-deposition of silicon with rare earth elements (REEs) and aluminium in the fern Dicranopteris linearis from China - Wen-Shen Liu; Hong-Xiang Zheng; Mei-Na Guo; Chang Liu; Hermine Huot; Jean Louis Morel; Antony van der Ent; Ye-Tao Tang; Rong-Liang Qiu (Plant and Soil, 2019)

Study on the grossular rabbit with high hardness excavated from Yin Ruins, Anyang, China - Rong Wang; Lu Cai; Tian-tian Bao; Ji-gen Tang; Chang-sui Wang (Archaeological and Anthropological Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Independent and Combined Effects of Chronic HIV-Infection and Tobacco Smoking on Brain Microstructure - Huajun Liang; Linda Chang; Rong Chen; Kenichi Oishi; Thomas Ernst (Journal of Neuroimmune Pharmacology, 2018)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Transcriptional and translational responses of rapeseed leaves to red and blue lights at the rosette stage - Sheng-xin Chang; Chu Pu; Rong-zhan Guan; Min Pu; Zhi-gang Xu (Journal of Zhejiang University-SCIENCE B, 2018)

Novel approach to integrated DNA adductomics for the assessment of in vitro and in vivo environmental exposures - Yuan-Jhe Chang; Marcus S. Cooke; Chiung-Wen Hu; Mu-Rong Chao (Archives of Toxicology, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Poecilostomatoid copepods associated with two species of widely distributed corals, Galaxea astreata (Lamarck, 1816) and Galaxea fascicularis (Linnaeus 1767), in the South China Sea - Yu-Rong Cheng; Chang-Feng Dai (Marine Biodiversity, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

Expression and Role of Voltage-Gated Sodium Channels in Human Dorsal Root Ganglion Neurons with Special Focus on Nav1.7, Species Differences, and Regulation by Paclitaxel - Wonseok Chang; Temugin Berta; Yong Ho Kim; Sanghoon Lee; Seok-Yong Lee; Ru-Rong Ji (Neuroscience Bulletin, 2018)

p70S6K activation promotes the transdifferentiation of fibroblasts to myofibroblasts in pterygium tissue growth on the cornea - Xin-Rong Zhao; Ming-Chang Zhang; Hua-Tao Xie; Nan Ji; Le-Tian Sun (Biotechnology Letters, 2018)

The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Biopharmaceutical Evaluation and CMC Aspects of Oral Modified Release Formulations - Rong-Kun Chang; Neil Mathias; Munir A. Hussain (The AAPS Journal, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Spatial distribution of turbulent mixing in the upper ocean of the South China Sea - Xiao-Dong Shang; Chang-Rong Liang; Gui-Ying Chen (Ocean Science, 2017)
The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of the Luzon Strait, with an average dissipation rate and diapycnal diffusivity of 8.3 × 10−9 W kg−1 and 2.7 × 10−5 m2 s−1, respectively, almost 1 order of magnitude higher than those in the central and southern SCS. In the region to the west of the Luzon Strait, the water column was characterized by strong shear and weak stratification. Elevated dissipation rates (ε > 10−7 W kg−1) and diapycnal diffusivities (κ > 10−4 m2 s−1), induced by shear instability, occurred in the water column. In the central and southern SCS, the water column was characterized by strong stratification and weak shear and the turbulent mixing was weak. Internal waves and internal tides generated near the Luzon Strait are expected to make a dominant contribution to the strong turbulent mixing and shear in the region to the west of the Luzon Strait. The observed dissipation rates were found to scale positively with the shear and stratification, which were consistent with the MacKinnon–Gregg model used for the continental shelf but different from the Gregg–Henyey scaling used for the open ocean.

Green Synthesis of Sucrose Laurate Under Different Ultrasonic Frequencies - Fang-xue Hang; Chang-rong Shi; Yong-shi Xu; Hai-qin Lu; Cai-feng Xie; Kai Li (Sugar Tech, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Observations of the turbulent kinetic energy dissipation rate in the upper central South China Sea - Chang-Rong Liang; Gui-Ying Chen; Xiao-Dong Shang (Ocean Dynamics, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Exploration of cultivable fungal communities in deep coal‐bearing sediments from ∼1.3 to 2.5 km below the ocean floor - Chang‐Hong Liu; Xin Huang; Tian‐Ning Xie; Ning Duan; Ya‐Rong Xue; Tan‐Xi Zhao; Mark A. Lever; Kai‐Uwe Hinrichs; Fumio Inagaki (Environmental Microbiology, 2017)
Summary Although subseafloor sediments are known to harbour a vast number of microbial cells, the distribution, diversity, and origins of fungal populations remain largely unexplored. In this study, we cultivated fungi from 34 of 47 deep coal‐associated sediment samples collected at depths ranging from 1289 to 2457 m below the seafloor (mbsf) off the Shimokita Peninsula, Japan (1118 m water depth). We obtained a total of 69 fungal isolates under strict contamination controls, representing 61 Ascomycota (14 genera, 23 species) and 8 Basidiomycota (4 genera, 4 species). Penicillium and Aspergillus relatives were the most dominant genera within the Ascomycetes, followed by the members of genera Cladosporium , Hamigera , Chaetomium , Eutypella , Acremonium , Aureobasidium , Candida , Eurotium , Exophiala , Nigrospora , Bionectria and Pseudocercosporella . Four Basidiomycota species were identified as genera Schizophyllum , Irpex , Bjerkandera and Termitomyces . Among these isolates, Cladosporium sphaerospermum and Aspergillus sydowii relatives were isolated from a thin lignite coal‐sandstone formation at 2457 mbsf. Our results indicate that these cultivable fungal populations are indigenous, originating from past terrigenous environments, which have persisted, possibly as spores, through ∼20 million years of depositional history.

Pteleifolols A–E, acetophenone di-C-glycosides and a benzopyran dimer from the leaves of Melicope pteleifolia - Ken-ichi Nakashima; Naohito Abe; Fang-Rong Chang; Makoto Inoue; Masayoshi Oyama (Journal of Natural Medicines, 2017)

Effects of β-glucan on ROS production and energy metabolism in yellow croaker (Pseudosciaena crocea) under acute hypoxic stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Jia-Lang Zheng; Chang-Wen Wu; Rong Cai (Fish Physiology and Biochemistry, 2016)

A bioeroding foraminifer, Hyrrokkin sarcophaga, on deepwater corals from the South China Sea - Yu-Rong Cheng; Chang-Feng Dai (Coral Reefs, 2016)

A preliminary study on the potential value of a novel integrated aquaculture system on water purification - Li-hong Chen; Rong-lian Xing; Ai-li Jiang; Li Teng; Chang-hai Wang (Aquaculture International, 2016)

Steroidobacter flavus sp. nov., a microcystin-degrading Gammaproteobacterium isolated from soil - Zhi-Lian Gong; Chang-Feng Zhang; Rong Jin; Yu-Qin Zhang (Antonie van Leeuwenhoek, 2016)

Hairy root induction and polysaccharide production of medicinal plant Callerya speciosa Champ. - Shao-chang Yao; Long-hua Bai; Zu-zai Lan; Mei-qiong Tang; Yong-jin Zhai; Hao Huang; Rong-chang Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Isolation and characterization of the marine algicidal bacterium Pseudoalteromonas S1 against the harmful alga Akashiwo sanguinea - Hong-Ye Sun; Yu Zhang; Hui-Rong Chen; Chang-Xing Hu; Hui Li; Zhang-Li Hu (Marine Biology, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Sulfuretin induces osteoblast differentiation through activation of TGF-β signaling - No-Joon Song; So-Mi Kwon; Suji Kim; Hyang-Jin Yoon; Cho-Rong Seo; Byunghyun Jang; Seo-Hyuk Chang; Jin-Mo Ku; Jeong-Soo Lee; Ki-Moon Park; Joung-Woo Hong; Geun Hyung Kim; et al. (Molecular and Cellular Biochemistry, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Erratum to: Generic Development of Topical Dermatologic Products: Formulation Development, Process Development, and Testing of Topical Dermatologic Products - Rong-Kun Chang; Andre Raw; Robert Lionberger; Lawrence Yu (The AAPS Journal, 2015)

A cross-kingdom assay model for evaluating estrogenic activity: application of transgenic Arabidopsis thaliana callus - Yu-Chi Tsai; Wan-Chun Lai; Mohamed El-Shazly; Shang-Yu Chiang; Ken-Ichiro Hayashi; Yang-Chang Wu; Fang-Rong Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Complete genome sequence of a novel velarivirus infecting areca palm in China - Hongmei Yu; Shuishui Qi; Zhaoxia Chang; Qiqi Rong; Ibukun A. Akinyemi; Qingfa Wu (Archives of Virology, 2015)

Analysis of methylation-sensitive amplified polymorphism in different cotton accessions under salt stress based on capillary electrophoresis - Baohua Wang; Rong Fu; Mi Zhang; Zhenqian Ding; Lei Chang; Xinyu Zhu; Yafeng Wang; Baoxiang Fan; Wuwei Ye; Youlu Yuan (Genes & Genomics, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Rainfall–Runoff Research on Upland Fields and A Comparison Of Kinematic Wave and Improved Tank Models - Rong‐Song Chen; Kuo‐Hsien Yang; Shun‐Chun Chang (Irrigation and Drainage, 2015)
Taiwan is a small, populous island. Because little flat land remains available for building, a trend in hillside development has recently been observed. During the storm season, especially during typhoons, heavy rainfall is common; however, the volume of rainfall is difficult to predict. Heavy precipitation causes flash floods as surface and groundwater levels overwhelm drainage systems. Thus people living on, or close to, hills are at risk of experiencing flooding with little warning. We investigated two models to discuss their differences and impact of rainfall in upland locations. The tank model describes and simulates the hydrology of an area, and the kinematic wave model simulates rainfall at upland locations. We used two natural rainfall events that occurred in the Tai‐Chung basin as case studies for both models. We applied five statistical indexes, namely root mean squared error (RMSE), coefficient of efficiency (CE), percentage error of peak discharge (EQp), error in time to peak (ETp), and percentage error of total volume (EV) to evaluate and interpret hydraulic data and our simulation results. We determined both models to be applicable; the results showed the relative error in peak flow simulation for the upland tank model to be less than 10%. The total runoff forecasts for large‐scale typhoon rainfall exhibited large errors in both models. Less severe rainfall events produced lower percentage errors in both models. The simulated hydrograph was compared with the measured hydrograph, and little difference was observed in the performance of the models. However, the simulation results of the kinematic wave model were slightly more favourable, possibly because the more complex wave model included more parameters representing physiographic factors, such as the river flow parameters P and K , equivalent roughness values of N , the average slope values, and the infiltration values, thus increasing the accuracy of the simulation. The upland tank model did not require complex physiographic factor parameters; instead, the Multistar‐Powell method was used to model the upland tank model parameters to produce a simulated hydrograph, yielding results no less favourable than those produced using the kinematic wave model. In the absence of comprehensive measured data and physiographic factors, the upland tank model has practical uses. Copyright © 2015 John Wiley & Sons, Ltd.

Longikaurin E induces apoptosis of pancreatic cancer cells via modulation of the p38 and PI3K/AKT pathways by ROS - Hai-bo Cheng; Yun Bo; Wei-xing Shen; Xian-guo Ren; Jia-ni Tan; Zhi-rong Jia; Chang-Liang Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

MALDI-TOF MS analysis of the extracellular polysaccharides released by the diatom Thalassiosira pseudonana under various nutrient conditions - Xin-Xin Ai; Jun-Rong Liang; Ya-Hui Gao; Samuel Chun-Lap Lo; Fred Wang-Fat Lee; Chang-Ping Chen; Chun-Shan Luo; Chao Du (Journal of Applied Phycology, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Impacts of shape and height of upstream roof on airflow and pollutant dispersion inside an urban street canyon - Yuan-dong Huang; Wen-rong He; Chang-Nyung Kim (Environmental Science and Pollution Research, 2015)

Removal of antibiotics and antibiotic resistance genes in rural wastewater by an integrated constructed wetland - Jun Chen; You-Sheng Liu; Hao-Chang Su; Guang-Guo Ying; Feng Liu; Shuang-Shuang Liu; Liang-Ying He; Zhi-Feng Chen; Yong-Qiang Yang; Fan-Rong Chen (Environmental Science and Pollution Research, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

An improved SCGM(1,m) model for multi-point deformation analysis - Qi-jie Wang; Chang-cheng Wang; Rong-an Xie; Xin-qing Zhang; Jian-jun Zhu (Geosciences Journal, 2014)

Serological report of pandemic and seasonal human influenza virus infection in dogs in southern China - Xin Yin; Fu-Rong Zhao; Dong-Hui Zhou; Ping Wei; Hui-Yun Chang (Archives of Virology, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

A new species of chondracanthid copepod parasitic in the pharynx of hagfishes (Myxiniformes: Myxinidae) from off Taiwan - Yu-Rong Cheng; Hao-Yuan Luo; Chang-Feng Dai; Hsiu-Hui Shih (Systematic Parasitology, 2014)

Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2014)

Characteristics of endogenous γ-aminobutyric acid (GABA) in human platelets: functional studies of a novel collagen glycoprotein VI inhibitor - Kuan-Hung Lin; Wan-Jung Lu; Shwu-Huey Wang; Tsorng-Harn Fong; Duen-Suey Chou; Chao-Chien Chang; Nen-Chung Chang; Yung-Chen Chiang; Shih-Yi Huang; Joen-Rong Sheu (Journal of Molecular Medicine, 2014)

Light-regulated phosphorylation of maize phosphoenolpyruvate carboxykinase plays a vital role in its activity - Qing Chao; Xiao-Yu Liu; Ying-Chang Mei; Zhi-Fang Gao; Yi-Bo Chen; Chun-Rong Qian; Yu-Bo Hao; Bai-Chen Wang (Plant Molecular Biology, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Soil nitrification and foliar δ15N declined with stand age in trembling aspen and jack pine forests in northern Alberta, Canada - Ya-Lin Hu; En-Rong Yan; Woo-Jung Choi; Francis Salifu; Xiao Tan; Z. Chi Chen; De-Hui Zeng; Scott X. Chang (Plant and Soil, 2014)

Genetic engineering techniques for lactic acid bacteria: construction of a stable shuttle vector and expression vector for β-glucuronidase - Shiao-Ming Chang; Tsong-Rong Yan (Biotechnology Letters, 2014)

The role of Mn oxide doping in phosphate removal by Al-based bimetal oxides: adsorption behaviors and mechanisms - Kun Wu; Ting Liu; Chao Ma; Bing Chang; Rong Chen; Xiaochang Wang (Environmental Science and Pollution Research, 2014)

Cloning and expression characterization of the chicken Piwil1 gene - Rong Chen; Guobin Chang; Aiqin Dai; Teng Ma; Fei Zhai; Mingxiu Xia; Lu Liu; Jianchao Li; Dengke Hua; Guohong Chen (Molecular Biology Reports, 2013)

Effect of Hyperoxia on the Viability and Proliferation of the Primary Type II Alveolar Epithelial Cells - Xiu-xiang Liu; Xiu-rong Yu; Xiu-hong Jia; Ke-xuan Wang; Zheng-yan Yu; Chang-jun Lv (Cell Biochemistry and Biophysics, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Generic Development of Topical Dermatologic Products, Part II: Quality by Design for Topical Semisolid Products - Rong-Kun Chang; Andre Raw; Robert Lionberger; Lawrence Yu (The AAPS Journal, 2013)

Dynamics of soil and root C stocks following afforestation of croplands with poplars in a semi-arid region in northeast China - Ya-Lin Hu; De-Hui Zeng; Scott X. Chang; Rong Mao (Plant and Soil, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Cloning, characterization and widespread expression analysis of testicular piRNA-like chicken RNAs - Ying Zhang; Jianchao Li; Rong Chen; Aiqin Dai; Deqin Luan; Teng Ma; Dengke Hua; Guohong Chen; Guobin Chang (Molecular Biology Reports, 2013)

MALDI-TOF MS analysis of the extracellular polysaccharides released by the diatom Thalassiosira pseudonana - Jun-Rong Liang; Xin-Xin Ai; Ya-Hui Gao; Chang-Ping Chen (Journal of Applied Phycology, 2013)

Response of leaf, sheath and stem nutrient resorption to 7 years of N addition in freshwater wetland of Northeast China - Rong Mao; Chang-Chun Song; Xin-Hou Zhang; Xian-Wei Wang; Zheng-Hai Zhang (Plant and Soil, 2013)

The Neuroprotective Effect of Overexpression of Calbindin-D28k in an Animal Model of Parkinson’s Disease - Hong-Hua Yuan; Ren-Jin Chen; Yu-Hua Zhu; Chang-Ling Peng; Xiao-Rong Zhu (Molecular Neurobiology, 2013)

Generic Development of Topical Dermatologic Products: Formulation Development, Process Development, and Testing of Topical Dermatologic Products - Rong-Kun Chang; Andre Raw; Robert Lionberger; Lawrence Yu (The AAPS Journal, 2013)

Volatile profile analysis and quality prediction of Longjing tea (Camellia sinensis) by HS-SPME/GC-MS - Jie Lin; Yi Dai; Ya-nan Guo; Hai-rong Xu; Xiao-chang Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Locating, monitoring, and characterizing typhoon-linduced landslides with real-time seismic signals - Honn Kao; Chih-Wen Kan; Rong-Yuh Chen; Chien-Hsin Chang; Andreas Rosenberger; Tzay-Chyn Shin; Pei-Ling Leu; Kai-Wen Kuo; Wen-Tzong Liang (Landslides, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

Characterization of the role of protein–cysteine residues in the binding with sodium arsenite - Yu-Ying Chang; Tai-Chih Kuo; Chun-Hua Hsu; Duen-Ren Hou; Yung-Hsi Kao; Rong-Nan Huang (Archives of Toxicology, 2012)

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Imprinting analysis of porcine MAGEL2 gene in two fetal stages and association analysis with carcass traits - Ling Guo; Mu Qiao; Chao Wang; Rong Zheng; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2012)

Comparison of Bacterial and Fungal Communities Between Natural and Planted Pine Forests in Subtropical China - Ming Nie; Han Meng; Ke Li; Jia-Rong Wan; Zhe-Xue Quan; Chang-Ming Fang; Jia-Kuan Chen; Bo Li (Current Microbiology, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

Molecular characterization of a wheat -Thinopyrum ponticum partial amphiploid and its derived substitution line for resistance to stripe rust - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Zu-Jun Yang (Journal of Applied Genetics, 2011)

Satellite altimeter observations of nonlinear Rossby eddy–Kuroshio interaction at the Luzon Strait - Quanan Zheng; Chang-Kuo Tai; Jianyu Hu; Hongyang Lin; Rong-Hua Zhang; Feng-Chun Su; Xiaofeng Yang (Journal of Oceanography, 2011)

Four new xarifiid copepods (Poecilostomatoida) associated with the scleractinian coral Pavona explanulata (Lamarck) from off Taiwan - Yu-Rong Cheng; Ju-shey Ho; Chang-Feng Dai (Systematic Parasitology, 2011)

Inorganic arsenic causes cell apoptosis in mouse cerebrum through an oxidative stress-regulated signaling pathway - Cheng Chien Yen; Tsung Jung Ho; Chin Ching Wu; Chun Fang Chang; Chin Chuan Su; Ya Wen Chen; Tzyy Rong Jinn; Tien Hui Lu; Po Wen Cheng; Yi Chang Su; Shing Hwa Liu; Chun Fa Huang (Archives of Toxicology, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Spartina alterniflora invasion increases soil inorganic nitrogen pools through interactions with tidal subsidies in the Yangtze Estuary, China - Rong Hao Peng; Chang Ming Fang; Bo Li; Jia Kuan Chen (Oecologia, 2011)

Plantagiolide F, a minor withanolide from Tacca plantaginea - Jun-Yun Yang; Chang-Xiang Chen; Rong-Hua Zhao; Xiao-Jiang Hao; Hai-Yang Liu (Natural Product Research, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Phylogenetics and Biogeography of the Phalaenopsis violacea (Orchidaceae) Species Complex Based on Nuclear and Plastid DNA - Chi-Chu Tsai; Chiou-Rong Sheue; Chih-Hsiung Chen; Chang-Hung Chou (Journal of Plant Biology, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Mitochondrial development and the influence of its dysfunction during rat adipocyte differentiation - Rong-hua Lu; Hong Ji; Zhi-guang Chang; Shang-shun Su; Gong-she Yang (Molecular Biology Reports, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Curcumin prevents liver fibrosis by inducing apoptosis and suppressing activation of hepatic stellate cells - Jian-Chang Shu; Ya-Jun He; Xia Lv; Guo-Rong Ye; Le-Xin Wang (Journal of Natural Medicines, 2009)

Orstomella yaliuensis n. sp., a xarifiid copepod (Crustacea) parasitic in the polyps of hump coral Porites lutea Milne Edwards & Haime off Taiwan - Yu-Rong Cheng; Ju-shey Ho; Chang-Feng Dai (Systematic Parasitology, 2009)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)

Preparation and Non-Invasive In-Vivo Imaging of Anti-Adhesion Barriers with Fluorescent Polymeric Marks - Shih-Rong Hsieh; Chi-Jung Chang; Tzong-Der Way; Po-Cheung Kwan; Tsung-Wei Hung (Journal of Fluorescence, 2009)

GSK-3β inhibitor modulates TLR2/NF-κB signaling following myocardial ischemia-reperfusion - Hao-Kao Gao; Zhong Yin; Rong-Qing Zhang; Jun Zhang; Feng Gao; Hai-Chang Wang (Inflammation Research, 2009)

Suppression pheromone and cockroach rank formation - Rong Kou; Huan-Wen Chang; Shu-Chun Chen; Hsiao-Yung Ho (The Science of Nature, 2009)

Changes in Soil Aggregate, Carbon, and Nitrogen Storages Following the Conversion of Cropland to Alfalfa Forage Land in the Marginal Oasis of Northwest China - Yong Zhong Su; Wen Jie Liu; Rong Yang; Xue Xiang Chang (Environmental Management, 2009)

Detection of plasmid-mediated IMP-1 metallo-β-lactamase and quinolone resistance determinants in an ertapenem-resistant Enterobacter cloacae isolate - Li-rong Chen; Hong-wei Zhou; Jia-chang Cai; Rong Zhang; Gong-xiang Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Respiratory face mask: a novel and cost-effective device for use during the application of myocardial ischemia in rats - Yuan Yuan; Fei Li; Yue-min Wang; Rong-qing Zhang; Li-ping Wei; Hai-chang Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Active extracts of wild fruiting bodies of Antrodia camphorata (EEAC) induce leukemia HL 60 cells apoptosis partially through histone hypoacetylation and synergistically promote anticancer effect of trichostatin A - Mei-Chin Lu; Ying-Chi Du; Jiunn-Jye Chuu; Shiuh-Lin Hwang; Pao-Chuan Hsieh; Chih-Sheng Hung; Fang-Rong Chang; Yang-Chang Wu (Archives of Toxicology, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Differential effects of a green tea-derived polyphenol (−)-epigallocatechin-3-gallate on the acidosis-induced decrease in the Ca2+ sensitivity of cardiac and skeletal muscle - Ying-Ming Liou; Shih-Chang Kuo; Shih-Rong Hsieh (Pflügers Archiv - European Journal of Physiology, 2008)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Sulfotransferase 1A1 and glutathione S-transferase P1 genetic polymorphisms modulate the levels of urinary 8-hydroxy-2′-deoxyguanosine in betel quid chewers - Ruey-Hong Wong; Chiung-Wen Hu; Ching-Ying Yeh; Mu-Rong Chao; Chin-Chun Chen; Jun-Huang Huang; Shih-Hsien Chang; Shin-I Lee; Hong-Shen Lee (Archives of Toxicology, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Identification of defense-related genes in rice responding to challenge by Rhizoctonia solani - Chang-Jiang Zhao; Ai-Rong Wang; Yu-Jun Shi; Liu-Qing Wang; Wen-De Liu; Zong-Hua Wang; Guo-Dong Lu (Theoretical and Applied Genetics, 2008)

Settlement, growth and survival of abalone, Haliotis discus hannai, in response to eight monospecific benthic diatoms - Rong-lian Xing; Chang-hai Wang; Xue-bin Cao; Ya-qing Chang (Journal of Applied Phycology, 2008)

Induction of apoptosis in rabbit oral mucosa by 1.23% acidulated phosphate fluoride gel - Chia-Ling Tsai; Jui-Wei Lin; Hsi-Kung Kuo; Ming-Hong Tai; Yi-Chen Wu; Chih-Rong Shyr; Pei-Chang Wu (Archives of Toxicology, 2008)

DNA sequence analysis of a cryptic plasmid pL2 from Lactococcus lactis subsp. lactis - Shiao-Ming Chang; Tsong-Rong Yan (Biotechnology Letters, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

Dietary separation between two blennies and the Pacific gregory in northern Taiwan: evidence from stomach content and stable isotope analyses - Cheng-Tze Ho; Shuh-Ji Kao; Chang-Feng Dai; Hwey-Lian Hsieh; Fuh-Kwo Shiah; Rong-Quen Jan (Marine Biology, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)

Characterization of a partial amphiploid between Triticum aestivum cv. Chinese Spring and Thinopyrum intermedium ssp. trichophorum - Yang Zu-Jun; Li Guang-Rong; Chang Zhi-Jian; Zhou Jian-Ping; Ren Zheng-Long (Euphytica, 2006)

SSR allelic variation in almond (Prunus dulcis Mill.) - Hua Xie; Yi Sui; Feng-Qi Chang; Yong Xu; Rong-Cai Ma (Theoretical and Applied Genetics, 2006)

Evaluation of the in Vivo Disintegration of Solid Dosage Forms of a Bile Acid Sequestrant in Dogs Using γ-Scintigraphy and Correlation to in Vitro Disintegration - Munir A. Hussain; Rong-Kun Chang; Erik Sandefer; Richard C. Page; George A. Digenis (Pharmaceutical Research, 2003)

Direct plantlet regeneration from the tuber of Stachys sieboldii - Wei Li; Huan-Huan Gao; Rong Lu; Guang-Qing Guo; Guo-Chang Zheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)

Development of an Unconventional In Vitro Drug Release Test Method for a Bile Acid Sequestrant, DMP 504, Tablet - Lei-Shu Wu; Timothy J. McCormick; Rong-Kun Chang; Josephine Pang; Tom McCummings; Miriam Ramos; Munir A. Hussain (Pharmaceutical Research, 1999)

The chirality selectivity in the uptake of platinum (II) complexes with 1,2-cyclohexanediamine isomers as carrier ligand by human erythrocytes - Juan Zou; Xiao Gai Yang; Rong Chang Li; Jing Fen Lu; Kui Wang (BioMetals, 1997)

Detection of the organophosphorus nerve agent sarin by a competitive inhibition enzyme immunoassay - Yong-xin Zhou; Qing-jin Yan; Yun-xiang Ci; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang; Yu-fen Zhao (Archives of Toxicology, 1995)

Production, characterization and application of monoclonal antibodies against the organophosphorus nerve agent Vx - Yun-xiang Ci; Yong-xin Zhou; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang (Archives of Toxicology, 1995)